Quantifying the efficiency of o-benzoquinones reaction with amino acids and related nucleophiles by cyclic voltammetry. (1st July 2020) - Li, Yuting; Qi, Haiping; Fan, Meiqi; Zhu, Zixing; Zhan, Shijie; Li, Lin; Li, Bing; Zhang, Xia; Zhao, Xianglong; Ma, Jingjing; Wang, Lifeng
Highlights: Cyclic voltammetry parameters significantly affect the reaction efficiency. Interaction of quinones with nucleophiles was more efficient at low scan rate. Nucleophilic group with lower pKa value had stronger reactivity towards o-quinone. Substituents on o-quinone ring affected its nucleophile trapping. Abstract: The reaction efficiency of o -benzoquinones with amines (L-lysine, Nα-acetyl-L-lysine, glycine, L-methionine and L-arginine), thiols (L-cysteine and Nα-acetyl-L-cysteine) and protein (bovine serum albumin) were determined at pH 5.0, 7.0 and 8.0 and scan rate of 10, 50 and 100 mV/s by cyclic voltammetry. Nucleophiles containing multiple nucleophilic groups and nucleophilic group possessing low pKa value would enhance the reactivity of nucleophiles towards o -benzoquinones. The reactivity of different o -benzoquinones with L-lysine/L-cysteine followed the order: protocatechuic acid quinone ≈ catechol quinone > 4-methylbenzoquinone ≈ caffeic acid quinone > rosmarinic acid quinone > chlorogenic acid quinone. The reactivity of quinones would be decreased by the steric hindrance of substituents on quinone ring, and it would also be weakened by enhancing electron cloud density of quinone ring. Adducts generated by the interaction of 4-methylbenzoquinone with amines and thiols were tentatively identified as amine-quinone adduct and thiol-phenol adduct respectively by UPLC-QTOF-MS/MS and cyclic voltammetry.